Elaboración de tres postres con chirimoya, babaco y plátano orito - Ramirez Flores, Stephany Gisselle (2025)
This study addresses the preparation of three Ecuadorian desserts using custard apple, babaco and orito banana, three tropical fruits native to Ecuador that, despite their high nutritional value, have been underutilized in local gastronomy. This problem responds to the lack of knowledge about their properties and application techniques, which limits their incorporation in confectionery and restricts the diversification of healthy products in the market. The general objective was to develop desserts that maximize the functional and nutritional value of these fruits, thus promoting their integration into the local gastronomic offer. The methodological approach was mixed. Surveys applied to 169 consumers in Quito were used to obtain quantitative data on the acceptance of these desserts and interviews with pastry experts were used to gather qualitative information on their perception and viability. In addition, experimental techniques will be applied in the formulation and sensory evaluation of the desserts, considering aspects such as flavor and texture. The results highlight a high acceptance of desserts incorporating these fruits, especially in options such as ice cream, espumillas, flans, breads and emborrajados. Consumers valued their tropical flavor, while experts highlighted the versatility of these fruits to innovate in traditional recipes. In addition, the research shows the potential of these fruits to highlight Ecuador's gastronomic identity and their contribution to a sustainable production model. It is concluded that cherimoya, babaco and orito banana have unique properties that position them as key ingredients in the creation of functional, healthy and innovative desserts. Their use promotes not only the diversification of local confectionery, but also the sustainability and valorization of Ecuadorian gastronomic culture.